Why do governments use pay for performance? Contrasting theories and interview evidence. (September 2014) - Atkinson, Michael M.; Fulton, Murray; Kim, Boa
Abstract In Canada, pay‐for‐performance (PFP) systems to compensate senior public servants have been established in several jurisdictions despite arguments by academics who doubt their efficacy in public sector environments characterized by high levels of intrinsic motivation. This article traces the pattern of PFP in Canada and distinguishes among "aggressive, " "passive, " and "reluctant" regimes. It explores why PFP is growing in popularity despite its acknowledged limitations. We canvass three theoretical perspectives and review evidence from interviews with key officials in a number of jurisdictions. The article contributes to our knowledge of managerial innovations by revealing the variety of motivations behind PFP.